Knowledge, attitudes, and practice related to tooth loss and dentures among patients with dental arch deficiencies - Jing Sun; Junru Meng; Jianliang Shan; Huijun Lu; Wei Wei; Shengnan Zhang; Li Zhang (BMC, 2024)
Abstract Background Tooth loss is a common problem that affects many people worldwide. Exploring knowledge, attitude, and practice (KAP) among patients can identify barriers and challenges in following recommended practices, providing valuable insights for dental healthcare providers, policymakers, and researchers. This study aimed to explore the KAP of patients with dental arch deficiencies regarding tooth loss and dentures. Methods This web-based, cross-sectional study was conducted among patients with dental arch deficiencies using a self-designed questionnaire. Result 3166 valid questionnaires were included. Participants' mean KAP scores were 6.84 ± 2.27 (possible range: 0 ~ 12), 39.4 ± 3.72 (possible range: 9 ~ 45), and 27.7 ± 4.36 (possible range: 8 ~ 40), respectively. Multivariable logistic regression analysis showed that knowledge (OR = 1.383), employed (OR = 1.805), family history (OR = 2.158), and treatment (OR = 1.683) were independently associated with attitude. Moreover, knowledge (OR = 1.239), attitude (OR = 1.250), female (OR = 0.619), age (OR = 0.967), college/bachelor (OR = 0.373), and master and above degree (OR = 0.418), employed (OR = 0.554) or student (OR = 0.434), with 10,001-20,000 Yuan household income per month (OR = 0.492), have been married (OR = 0.609), smoking (OR = 0.595), drinking (OR = 0.397), disease duration (OR = 0.972), with family history (OR = 1.676), and with treatment (OR = 3.492) were independently associated with practice (all P < 0.05). Conclusion Patients with dental arch deficiencies have insufficient knowledge, positive attitudes, and moderate practice toward tooth loss and dentures, which might be affected by multiple demographic factors.